2006
DOI: 10.1189/jlb.0205084
|View full text |Cite
|
Sign up to set email alerts
|

CpG-C ISS-ODN activation of blood-derived B cells from healthy and chronic immunodeficiency virus-infected macaques

Abstract: Cytosine-phosphate-guanine class C (CpG-C) immunostimulatory sequence oligodeoxynucleotides (ISS-ODNs) activate human B cells and dendritic cells (DCs), properties that suggest potential use as a novel adjuvant to enhance vaccine efficacy. After demonstrating that the CpG-C ISS-ODN C274 activates macaque DCs, we examined in vitro activation of macaque B cells by C274 as a prelude to evaluation of this molecule as an adjuvant in the testing of candidate human immunodeficiency virus vaccines in the rhesus macaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 93 publications
4
26
1
Order By: Relevance
“…Previous studies showed that CpG-B ISS-ODNs boosted vaccine efficacy in nonhuman primates (49 -55), but until recently there were no reports of CpG-C ISS-ODN usage in macaques (56). We found that the CpG-C ISS-ODN C274 activates macaque blood-derived DCs (17) and B cells (57) in vitro. This is supported by a recent report from Abel et al (58), documenting the responses of macaque blood and lymphoid PDCs to the different classes of CpG ISS-ODNs.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 56%
See 4 more Smart Citations
“…Previous studies showed that CpG-B ISS-ODNs boosted vaccine efficacy in nonhuman primates (49 -55), but until recently there were no reports of CpG-C ISS-ODN usage in macaques (56). We found that the CpG-C ISS-ODN C274 activates macaque blood-derived DCs (17) and B cells (57) in vitro. This is supported by a recent report from Abel et al (58), documenting the responses of macaque blood and lymphoid PDCs to the different classes of CpG ISS-ODNs.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 56%
“…3. Just as for blood cells (17,57), in vitro exposure to C274 induced the most prominent up-regulation of CD80 and (less so) CD86 on Lin Ϫ HLA-DR ϩ CD123 ϩ PDCs and B cells in the LNC cultures (Fig. 3).…”
Section: Up-regulation Of Costimulatory Molecules On Dcs and B Cells mentioning
confidence: 99%
See 3 more Smart Citations